1999
DOI: 10.2190/74t0-8fmh-frj7-76na
|View full text |Cite
|
Sign up to set email alerts
|

The Psychophysiological Differentiation of Actual, Imagined, and Recollected Anger

Abstract: Heart rate and skin resistance responses from thirty-six participants (5 men and 31 women) were recorded to determine if significant differences exist among three different types of inducing anger including the present state of anger (Actual Anger), anger elicited through imagination (Imagined Anger), and anger elicited through recollection (Recollected Anger). An analysis of variance indicated significant differences for heart rate among the three methods, F(2,35) = 8.75, p = .0009, but not for skin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
16
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
(111 reference statements)
6
16
1
Order By: Relevance
“…A meta-analysis found that visual stimuli have a smaller effect on anger than autobiographical recall, situational procedures, and imagery (Lench et al, 2011). Additional research found that situational procedures are more effective than visual stimuli, but that imagery and recall are more effective than situational procedures (Foster, Smith, & Webster, 1999;Lobbestael et al, 2008). We therefore recommend imagery or recall as the strongest techniques for inducing anger, followed by situational procedures, visual stimuli, and music.…”
Section: Imagerymentioning
confidence: 80%
“…A meta-analysis found that visual stimuli have a smaller effect on anger than autobiographical recall, situational procedures, and imagery (Lench et al, 2011). Additional research found that situational procedures are more effective than visual stimuli, but that imagery and recall are more effective than situational procedures (Foster, Smith, & Webster, 1999;Lobbestael et al, 2008). We therefore recommend imagery or recall as the strongest techniques for inducing anger, followed by situational procedures, visual stimuli, and music.…”
Section: Imagerymentioning
confidence: 80%
“…While some investigations successfully differentiated emotions psychophysiologically, others did not. In addition, even among those investigations that were successful, the findings were in many instances contradictory [21]. The present authors have suggested that these conflicting and incongruent findings may be the result of the myriad of different methodologies used to induce emotions [21].…”
mentioning
confidence: 78%
“…In addition, even among those investigations that were successful, the findings were in many instances contradictory [21]. The present authors have suggested that these conflicting and incongruent findings may be the result of the myriad of different methodologies used to induce emotions [21]. Many of the aforementioned investigations have utilized different methods to induce emotional arousal.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Further, this implication becomes especially pertinent when considering the fact that most investigations using emotional memories have typically not reported either placing any constraints on the ages of the memories to be recalled 1,3,7,[9][10]12,[16][17][18] or specified a specific age for the memories. 2,[4][5][6][13][14] Realizing the potentially serious implications of a relation between varying ages of emotional memories and psychophysiological responding, Foster and Webster 5 conducted an investigation to determine whether such a relation existed. The findings of this investigation indicated that a significant positive correlation existed between changes in skin conductance and ages of both angry and mirthful memories.…”
mentioning
confidence: 99%